Biobanking in LMIC settings for infectious diseases: Challenges and enablers - Sameera Ezzat; Ruzica Biga; Zisis Kozlakidis (Elsevier, 2022)
Biobanking facilities are well established in high-income settings, where substantial funding has been invested in infrastructure. In contrast, such facilities are much less developed in resource-restricted settings. However, low-and middle-income countries (LMICs) still face a disproportionately high infectious diseases burden. Thus, the further development of infrastructure facilities, including biobanks is warranted as an important component of this unfolding clinical research environment. This perspective manuscript summarises the challenges and enablers for biobanking in LMICs, with a particular focus on infectious diseases, incorporating some of the lessons learned from the recent coronavirus disease 2019 (COVID-19) pandemic.